THE RELATION SHIPS AND FUNCTIONS OF SCHOOLS OF PUBLIC HELATH AND DEPARTMENTS OF PREVENTIVE AND SOCIAL MEDICINE IN UNDERGRADUATE MEDICAL SCHOOLS - M.H Chamseddine Mofidi; Garegin Saroukhanian (Tehran University of Medical Sciences, 1972)
In spite of all the progress and achievements in the establish meat and development of health services in the world to date there is still a great and urgent need for new system of delivery of health and medical care particularly in developing counties. Until now universities and medical institutions have been training high level professional personnel for delivery of hospital based Medicaid care. But the health services needed in the country can not be met only through hospitals. In many parts of the world these services have evolved as a result of educational and research activities of the schools of Public health. Generally speaking the curriculum of the schools of medicine for the orientation of their graduates in social and preventive medicine looks adequate. Unfortunately this is true only in theory. In practice this has never been achieved, because of the attention of these units, (both from the standpoint of administration and management as well as objectives and operational support) has been always concentrated to hospital teaching.